Education Perception, Experience, and Anxiety Level Among Undergraduate Dental Students in Malaysia During the Covid 19 Pandemic - Kamar Affendi, Nur Hafizah; Md Bohari, Nor Faezah; Salihan, Ameer Razek; Rosman, Nur Aishah (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: This study aims to explore the dental students’ educational experience, the protocol consideration after school reopening and their physical health during the COVID-19 pandemic. Secondly, to evaluate the anxiety level of dental students during the COVID-19 pandemic. Method: A cross-sectional survey was distributed with a hyperlink, reported as frequencies and percentages. A univariate analysis was used to explore the significant associations between demographic variables and anxiety levels. The risk factor was also identified using regression analysis. A two-tailed p<0.25 was considered significant. Results: A total of 333 respondents participated in the survey. Half of the respondents (42.3%) were comfortable with distance learning but worried about passing their examination and completing their clinical requirements. The transitioning to the online course by the lecturer was documented as effective. Despite missing academic sessions, only 15.3% were willing to replace the loss of educational experience. The majority of students (85.9%) believed that masks should be worn in school, but varied perceptions on wearing gloves and frequent COVID-19 testing. For physical health, mostly concerned about contracting the virus after the school reopens. For their anxiety level, nearly half have mild (n=99), moderate (n=55), and severe (n=36) levels. The factors were mainly associated with gender, household income, type of university, and respondent’s accommodation. Conclusion: As positive feedback was recorded towards online learning, constant improvement is needed to ensure the possibility of hybrid learning, even after the pandemic. The physical and psychological health of dental students should be a priority, to ensure a smooth transition during these unprecedented circumstances. References Shah AM, Safri SA, Thevadas R, Noordin N, Rahman A, Sekawi Z, Ideris A, Sultan MH. COVID-19 outbreak in Malaysia: Actions taken by the Malaysian government. International Journal of Infectious Diseases. 2020;97:108-16. Pan Y, Liu H, Chu C, Li X, Liu S, Lu S. Transmission routes of SARS-CoV-2 and protective measures in dental clinics during the COVID-19 pandemic. Am J Dent. 2020;33:129-34. Sundarasen S, Chinna K, Kamaludin K, Nurunnabi M, Baloch G, Khoshaim H, Hossain SA, Sukayt A. Psychological Impact of COVID-19 and Lockdown among University Students in Malaysia: Implications and Policy Recommendations. International Journal of Environmental Research and Public Health. 2020;17:6206. Hung M, Licari F, Hon E, Lauren E, Su S, Birmingham W, Wadsworth L, Lassetter J, Graff T, Harman W, Carroll W, Lipsky M. In an era of uncertainty: Impact of COVID‐19 on dental education. Journal of Dental Education. 2020;85:148-56. Yau E, Ping N, Shoesmith W, James S, Hadi N, Loo J. The behaviour changes in response to COVID-19 pandemic within Malaysia. The Malaysian Journal of Medical Sciences: MJMS. 2020;27:45. Andrews N, Stowe J, Kirsebom F, Toffa S, Rickeard T, Gallagher E, Gower C, Kall M, Groves N, O’connell A, Simons D, Blomquist P, Zaidi A, Nash S, Iwani Binti Abdul Aziz N, Thelwall S, Dabrera G, Myers R, Amirthalingam G, Gharbia S, Barrett J, Elson R, Ladhani S, Ferguson N, Zambon M, Campbell CJ, Brown K, Hopkins S, Chand M, Ramsay M, Lopez Bernal J. Covid-19 Vaccine Effectiveness against the Omicron (B.1.1.529) Variant. New England Journal of Medicine. 2022;386:1532-46. Loch C, Kuan IJ, Elsalem L, Schwass D, Brunton P, Jum’ah A. COVID‐19 and dental clinical practice: Students and clinical staff perceptions of health risks and educational impact. Journal of Dental Education. 2021;85:44-52. Özdede M, Sahin S. Views and anxiety levels of Turkish dental students during the COVID-19 pandemic. Journal of Stomatology. 2020;73:123-8. Son C, Hegde S, Smith A, Wang X, Sasangohar F. Effects of COVID-19 on College Students’ Mental Health in the United States: Interview Survey Study. Journal of Medical Internet Research. 2020;22:e21279. Agius A, Gatt G, Vento Zahra E, Busuttil A, Gainza‐cirauqui M, Cortes AG, Attard N. Self‐reported dental student stressors and experiences during the COVID‐19 pandemic. Journal of Dental Education. 2021 Feb;85:208-15. Cao W, Fang Z, Hou G, Han M, Xu X, Dong J, Zheng J. The psychological impact of the COVID-19 epidemic on college students in China. Psychiatry Research. 2020;287:112934. Zhao B, Kong F, Aung M, Yuasa M, Nam E. Novel coronavirus (COVID-19) knowledge, precaution practice, and associated depression symptoms among university students in Korea, China, and Japan. International journal of environmental research and public health. 2020;17:6671. Wathelet M, Duhem S, Vaiva G, Baubet T, Habran E, Veerapa E, Debien C, Molenda S, Horn M, Grandgenèvre P, Notredame C. Factors associated with mental health disorders among university students in France confined during the COVID-19 pandemic. JAMA network open. 2020 Oct 1;:e2025591. Hakami Z, Khanagar S, Vishwanathaiah S, Hakami A, Bokhari A, Jabali A, Alasmari D, Aldrees A. Psychological impact of the coronavirus disease 2019 (COVID‐19) pandemic on dental students: A nationwide study. Journal of Dental Education. 2021 Apr;85:494-503. Fallahi H, Keyhan S, Zandian D, Kim S, Cheshmi B. Being a front-line dentist during the Covid-19 pandemic: a literature review. Maxillofacial Plastic and Reconstructive Surgery. 2020;42:1-9. Council M. MDA Safety Advisory to Dental Practitioners during the current Concern of COVID -19 Infection during Conditional/Recovery -Movement Control Order. 2020;. Etajuri E, Mohd N, Naimie Z, Ahmad N. Undergraduate dental students’ perspective of online learning and their physical and mental health during COVID-19 pandemic. PLOS ONE. 2022 Jun 16;17:e0270091. Lestari W, Yazid N, Azhar Z, Ismail A, Sukotjo C. Impact of COVID-19 on Malaysian dental students’ physical, mental, financial and academic concerns. BMC Oral Health. 2022 Dec;22:1-9. Cuschieri S. The STROBE guidelines. Saudi Journal of Anaesthesia. 2019;13:31. Toussaint A, Hüsing P, Gumz A, Wingenfeld K, Härter M, Schramm E, Löwe B. Sensitivity to change and minimal clinically important difference of the 7-item Generalized Anxiety Disorder Questionnaire (GAD-7). Journal of Affective Disorders. 2020;265:395-401. Grubic N, Badovinac S, Johri A. Student mental health in the midst of the COVID-19 pandemic: A call for further research and immediate solutions. International Journal of Social Psychiatry. 2020;66:517-8. Azab E, Aboalshamat K. Attitudes, Barriers, and Experiences Regarding E-Learning and Dental Education during COVID-19 Pandemic. The Open Dentistry Journal. 2021;15:464-72. Prieto D, Tricio J, Cáceres F, Param F, Meléndez C, Vásquez P, Prada P. Academics’ and students’ experiences in a chilean dental school during the COVID‐19 pandemic: A qualitative study. European Journal of Dental Education. 2021;25:689-97. Machado R, Bonan PF, Perez DDC, Martelli Júnior H. COVID-19 pandemic and the impact on dental education: discussing current and future perspectives. Brazilian Oral Research. 2020 Jun 29;34. Chick R, Clifton G, Peace K, Propper B, Hale D, Alseidi A, Vreeland T. Using Technology to Maintain the Education of Residents During the COVID-19 Pandemic. Journal of Surgical Education. 2020;77:729-32. Shailaja B, Shetty V, Chaudhury S, Thyloth M. Exploring cyberchondria and its associations in dental students amid COVID-19 infodemic. Industrial Psychiatry Journal. 2020;29:257. Aragão MB, Gomes FF, Paixão‐de‐melo L, Corona SM. Brazilian dental students and COVID‐19: A survey on knowledge and perceptions. European Journal of Dental Education. 2022;26:93-105. Van Schalkwyk F. Reflections on the public university sector and the covid-19 pandemic in South Africa. Studies in Higher Education. 2021;46:44-58. Al-Maskari A, Al-Riyami T, Kunjumuhammed S. Students academic and social concerns during COVID-19 pandemic. Education and Information Technologies. 2022;27:1-21. Di Domenico L, Pullano G, Sabbatini C, Boëlle P, Colizza V. Modelling safe protocols for reopening schools during the COVID-19 pandemic in France. Nature Communications. 2021;12. Deery C. The COVID-19 pandemic: implications for dental education. Evidence-Based Dentistry. 2020;21:46-7. Alharbi A, Alharbi S, Alqaidi S. Guidelines for dental care provision during the COVID-19 pandemic. The Saudi Dental Journal. 2020;32:181-6. Savitsky B, Findling Y, Ereli A, Hendel T. Anxiety and coping strategies among nursing students during the covid-19 pandemic. Nurse Education in Practice. 2020 Jul 1;46:102809. Debowska A, Horeczy B, Boduszek D, Dolinski D. A repeated cross-sectional survey assessing university students’ stress, depression, anxiety, and suicidality in the early stages of the COVID-19 pandemic in Poland. Psychological Medicine. 2020 Oct 2;52:3744-7. Li Y, Li J, Yang Z, Zhang J, Dong L, Wang F, Zhang J. Gender Differences in Anxiety, Depression, and Nursing Needs Among Isolated Coronavirus Disease 2019 Patients. Frontiers in Psychology. 2021 Jun 7;12:615909. Basudan S, Binanzan N, Alhassan A. Depression, anxiety and stress in dental students. International Journal of Medical Education. 2017;8:179-86. Coughlan J, Timuş D, Crnic T, Srdoč D, Halton C, Dragan I. Impact of COVID‐19 on dental education in Europe: The students’ perspective. European Journal of Dental Education. 2022 Aug;26:599-607.